Spiritual beliefs in early 20th century Arab culture amidst a pandemic: Taha Hussein's Al-Ayyam - Nur Asyiqin Zohkarnain,; Firuz-Akhtar Lubis,; Zulkarnain Mohamed, (Penerbit Universiti Kebangsaan Malaysia, 2025)
Spirituality often emerges as a source of resilience and identity formation for marginalised communities, particularly during times of crisis such as pandemics. Yet, the cultural dimensions of spiritual responses in literature remain underexplored, especially in narratives shaped by historical, social, and religious complexities. This study examines al-Ayyam, the autobiographical novel by Taha Hussein, as a literary lens to understand how spiritual practices and beliefs function as coping mechanisms in the face of adversity. Set in early 20th-century Egypt, the novel reflects the lived experiences of a socially and physically marginalised individual navigating a society marked by tradition, inequality, and upheaval. Using a qualitative content analysis guided by the Symbiotic Cultural Framework (SCF), this research explores the novel’s portrayal of spiritual resilience, communal identity, and cultural continuity during a pandemic. The findings reveal how spiritual elements rituals, beliefs, and inner faith are intricately woven into the narrative to underscore both personal survival and collective endurance. By highlighting the intersection of marginalisation and spirituality in al-Ayyam, this study contributes to ongoing discussions in literary and cultural studies on how literature gives voice to the silenced and sustains cultural memory in times of crisis.